Effect of the bionic blade on the flow field of a straight-bladed vertical axis wind turbine. (1st November 2022) - Zhang, Yanfeng; Li, Qing'an; Zhu, Xinyu; Song, Xiaowen; Cai, Chang; Zhou, Teng; Kamada, Yasunari; Maeda, Takao; Wang, Ye; Guo, Zhiping
Abstract: This paper uses the Particle Image Velocimetry technique through wind tunnel experiments to investigate the spanwise velocity and vortex characteristics of a straight-bladed vertical axis wind turbine (VAWT) and to verify the reliability of the numerical simulation model. The aerodynamic forces are obtained by a multiport pressure measurement device. To assess the flow field of VAWT with bionic blades, this paper compares results between numerical simulations and experiments. Different flow field characteristics of wind turbines have been found in the baseline blades and bionic blades. The research shows that the bionic blade can suppress the influence of the tip vortex on the velocity of the cross-section z /( H /2) = 1.0, and the wake recovery velocity of VAWT with bionic blades is lower than that with baseline blades. By comparing the tangential force coefficients of the blades, it has been found that the tangential force of the bionic blades increases in azimuth angle regions 30°< θ  < 116° and 193°< θ  < 301°. It has also been proven that the aerodynamic performance of the bionic blade is slightly better than the baseline blades at TSR = 2.19. This study provides a better understanding of the development of aerodynamic forces and vortex characteristics through torque and velocity measurements. Highlights: The wind velocity around the blades are measured by the Particle Image Velocimetry (PIV) device. Wake characteristics of the VAWT with bionic blades are investigated by contrasting with standard blades. The bionic structure can suppress the influence of the tip vortex on the airflow. The wake recovery of the VAWT with bionic blades is slower than that with standard blades. The average power coefficient of the VAWT with bionic blades is bigger than that with standard blades.